Українські зовнішньополітичні відносини у різні часи - Єфремова, А. С. (ХНУРЕ, 2019)
The title of the article is “Ukrainian external political relations”. The article provides the reader with some material on past political victories and failures of Ukraine. It is spoken in detail the period of adaptation of Ukraine. The text gives valuable information on reasons for Ukraine’s refusal of nuclear weapons.